2019
DOI: 10.1186/s12879-019-4601-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and temporal trends of leprosy in Uganda, 2012–2016: a retrospective analysis of public health surveillance data

Abstract: BackgroundLeprosy is a neglected disease that poses a significant challenge to public health in Uganda. The disease is endemic in Uganda, with 40% of the districts in the country affected in 2016, when 42 out of 112 districts notified the National Tuberculosis and Leprosy Program (NTLP) of at least one case of leprosy. We determined the spatial and temporal trends of leprosy in Uganda during 2012–2016 to inform control measures.MethodsWe analyzed quarterly leprosy case-finding data, reported from districts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…23 from Brazil [ 11 33 ], 6 from India [ 34 – 39 ], 3 from China [ 40 42 ], 2 from Bangladesh [ 2 , 43 ] and Comoros [ 44 , 45 ]. One from Cambodia [ 46 ], Sri-Lanka [ 47 ], Cameroon [ 48 ], Venezuela [ 49 ], Bangladesh and Thailand [ 50 ], Indonesia [ 51 ], Argentina [ 52 ], and Uganda [ 53 ]. Three publications focussed on the global leprosy burden.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 from Brazil [ 11 33 ], 6 from India [ 34 – 39 ], 3 from China [ 40 42 ], 2 from Bangladesh [ 2 , 43 ] and Comoros [ 44 , 45 ]. One from Cambodia [ 46 ], Sri-Lanka [ 47 ], Cameroon [ 48 ], Venezuela [ 49 ], Bangladesh and Thailand [ 50 ], Indonesia [ 51 ], Argentina [ 52 ], and Uganda [ 53 ]. Three publications focussed on the global leprosy burden.…”
Section: Resultsmentioning
confidence: 99%
“…Only indicators with cut-off values are presented. Note: 2 out of 47 articles did not provide classification cut-off: Araujo et al 2017 [ 12 ] and Aceng et al 2019 [ 53 ] b classified as high transmission areas. …”
Section: Resultsmentioning
confidence: 99%
“…In this study, the floating leprosy cases were found to be increased dramatically after the implementation of the strategy, making it more difficult to find the cases. Under a low endemic situation, the distribution of newly detected cases remains unbalanced in most countries 25,26 . Meanwhile, most of the cases were diagnosed passively as reported by dermatologists 8,27 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, both fellows and staff have extensive experience in outbreak investigations and the associated administrative and political impact. Key outbreak preparedness and response activities have included those for Ebola virus disease [36,37], Marburg virus [37], plague, anthrax [38][39][40], measles [41][42][43][44][45][46], yellow fever [47], Rift Valley fever, malaria [48][49][50], typhoid, Crimean-Congo hemorrhagic fever [51], food poisoning [52,53], chemical poisoning [54,55], rabies [56], typhoid [57], leprosy [58], cholera [59][60][61], tuberculosis [62], podoconiosis [63], and many others [12]. These investigations have occurred countrywide and, at times, in collaboration with neighboring countries [52].…”
Section: Experiencementioning
confidence: 99%